2015
DOI: 10.1038/mp.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo imaging of grey and white matter neuroinflammation in Alzheimer’s disease: a positron emission tomography study with a novel radioligand, [18F]-FEPPA

Abstract: Our primary aim was to compare neuroinflammation in cognitively intact control subjects and patients with Alzheimer's disease (AD) by using positron emission tomography (PET) with translocator protein 18 kDa (TSPO)-specific radioligand [(18)F]-FEPPA. [(18)F]-FEPPA PET scans were acquired on a high-resolution research tomograph in 21 patients with AD (47- 81 years) and 21 control subjects (49-82 years). They were analyzed by using a 2-tissue compartment model with arterial plasma input function. Differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 69 publications
4
82
0
1
Order By: Relevance
“…As reported above, these bioactive lipid mediators are sufficient to reduce neuroinflammation in stroke, i.c.v. LPS, neuropathic pain models, and surgery-induced (Suridjan et al, 2015). Since n-3 PUFA modulate microglia markers such as Iba-1 as described above, future clinical studies in humans could image neuroinflammation following n-3 PUFA treatment and relate TSPO binding with the reduction with symptoms.…”
Section: As Most Studies Measured Only a Few Inflammatory Markers In mentioning
confidence: 96%
“…As reported above, these bioactive lipid mediators are sufficient to reduce neuroinflammation in stroke, i.c.v. LPS, neuropathic pain models, and surgery-induced (Suridjan et al, 2015). Since n-3 PUFA modulate microglia markers such as Iba-1 as described above, future clinical studies in humans could image neuroinflammation following n-3 PUFA treatment and relate TSPO binding with the reduction with symptoms.…”
Section: As Most Studies Measured Only a Few Inflammatory Markers In mentioning
confidence: 96%
“…Autoradiography studies demonstrated greater binding of 3 H-DAA1106 to TSPO in both a transgenic AD mouse model (Maeda et al, 2011) and in human tissue from AD brains (Gulyas et al, 2009). In addition, binding with 18 F-FEPPA was shown to be greater in AD patients than in controls in hippocampus and white matter regions such as internal capsule and cingulum bundle, as well as in prefrontal, temporal, parietal, and occipital cortices (Suridjan et al, 2015). Greater 18 F-FEPPA binding also correlated with worse performance on some cognitive measures (Suridjan et al, 2015).…”
Section: Neuroinflammation In Alzheimer’s Diseasementioning
confidence: 99%
“…In addition, binding with 18 F-FEPPA was shown to be greater in AD patients than in controls in hippocampus and white matter regions such as internal capsule and cingulum bundle, as well as in prefrontal, temporal, parietal, and occipital cortices (Suridjan et al, 2015). Greater 18 F-FEPPA binding also correlated with worse performance on some cognitive measures (Suridjan et al, 2015). Finally, in studies using 11 C-( R )-PK-11195 and 11 C-PBR28, TSPO binding was found to increase with progression of AD (Fan, Okello, Brooks, & Edison, 2015; Kreisl et al, 2016).…”
Section: Neuroinflammation In Alzheimer’s Diseasementioning
confidence: 99%
“…Human studies using these secondgeneration ligands have demonstrated increased TSPO expression in a variety of CNS disorders, including Alzheimer's disease [37], amyotrophic lateral sclerosis [34], and multiple sclerosis [38].…”
Section: Challenges Of Second-generation Tspo Pet Radioligandsmentioning
confidence: 99%